Neurokinin-1 receptor antagonists as novel antidepressants: trials and tribulations. - Hafizi, S; Chandra, P; Cowen, J (2007)
Based upon animal experiments and early clinical trials, neurokinin-1 receptor antagonists showed promise as novel antidepressants. Subsequently, however, more extensive clinical trials did not reveal evidence of efficacy in depression. The development of novel antidepressants will require a better understanding of the neural basis of antidepressant action in humans.